Cover Image. (19th April 2022) - Chardon, Nathalie Isabelle; Nabe‐Nielsen, Jacob; Assmann, Jakob Johan; Dyrholm Jacobsen, Ida Bomholt; Guéguen, Maya; Normand, Signe; Wipf, Sonja
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13498 "High resolution species distribution and abundance models cannot predict separate shrub datasets in adjacent Arctic fjords" by Chardon et al. The Nuup Kangerlua fjord in Southwest Greenland is topographically complex, with sparse to dense shrub species cover, making it a good candidate for high resolution spatial models. Image credit: Nathalie Chardon.